Examining Intrinsic and Extrinsic Motivation Factors among Graduate Employees in China - WANG, SHUXIN (2020)
The aim of this study is to examine the intrinsic and extrinsic factors that motivate graduate employees in China. Graduate employees play an important role especially in China. Thus, it is necessary for contemporary organizations to discover the difference between intrinsic and extrinsic motivation factor and adopt appropriate methods to motivate graduate employees, improve their performance and inspire their potentials. This study adopts quantitative research methods, using a 5-point Likert scale questionnaire to investigate 200 Chinese graduate employees. The data is analyzed by using SPSS software. The result shows that adequate earning is the most significant motivation factor for graduate employees in China followed by job security. Meanwhile, this study found that gender, organization type and education level are significantly related to motivation preference. This study will also discuss recommendation, limitations and future suggestions.